The Roles of Inflammation in Keloid and Hypertrophic Scars - Wang, Zheng-Cai; Zhao, Wan-Yi; Cao, Yangyang; Liu, Yan-Qi; Sun, Qihang; Shi, Peng; Cai, Jia-Qin; Shen, Xiao Z.; Tan, Wei-Qiang (Frontiers in Immunology, 2020)
The underlying mechanisms of wound healing are complex but inflammation is one of the determining factors. Besides its traditional role in fighting against infection upon injury, the characteristics and magnitude of inflammation have dramatic impacts on the pathogenesis of scar. Keloids and hypertrophic scars are pathological scars that result from aberrant wound healing. They are characterized by continuous local inflammation and excessive collagen deposition. In this review, we aim at discussing how dysregulated inflammation contributes to the pathogenesis of scar formation. Immune cells, soluble inflammatory mediators and the related intracellular signal transduction pathways are our three subtopics encompassing the events occurring in inflammation associated with scar formation. In the end, we enumerate the current and potential medicines and therapeutics for suppressing inflammation and limiting progression to scar. Understanding the initiation, progression and resolution of inflammation will provide insights into the mechanisms of scar formation and is useful for developing effective treatments.